Motivasi Orangtua dalam Memilih PAUD - Kale, Sartika; Koten, Angelikus Nama; Margiani, Kristin; Ga Riwu, Sri Rahayu (Education For All, 2022)
The problem of this study is the difference between the parents’ life and the school chosen for the child, so the aims of this study is to describe the factors that influence parents’ motivation in choosing PAUD in Gugus Pelangi, Kota Lama, Kupang. This study uses a quantitative approach with descriptive research and survey research methods. The research subjects were parents of students in PAUD in Gugus Pelangi add up 138 subjects. Data were collected using a questionnaire. The result showed that the factors that influence parents’ motivation to send their children to school is extrinsic factors are costs 80, school location and environment 69%, facilities 63%, school achievement 59%, vision and mission 47%, distance between school and house 33%. Intrinsic factor is parental understanding 59%. So these results indicate that the factor that most influences parents’ motivation in choosing schools for their children is the cost factor.